PENINGKATAN PENGETAHUAN PETUGAS AHLI TEKNOLOGI LABORATORIUM MEDIS (ATLM) DAN PERAWAT DI LABORATORIUM DIAGNOS DENPASAR TERKAIT MANAJEMEN LABORATORIUM ISO 9001:2015 - Anak Agung Ayu Eka Cahyani; Hendro Wahyudi; Anak Agung Sri Sanjiwani; Silvia Ni Nyoman Sintari; I Dewa Gede Candra Dharma (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
Laboratory management is an attempt to manage the laboratory. One of the quality management systems to ensure the quality of its management is to apply the ISO 9001:2015 standard. Laboratory Clinic Diagnos Denpasar is one of the intermediate level laboratories located in the center of Denpasar City. The Laboratory Clinic Diagnos Denpasar has only been opened since January 10, 2020 and is on its way to ISO 9001:2015 standard certification. The Community Activities are carried out in collaboration with DPW PATELKI Bali as a speaker for counseling for ATLM. The questionnaire was administered to measure ATLM's knowledge of ISO 9001:2015. The results of the questionnaire were tabulated using the Paired Sample-T Test with the result p value = 0.00. The result is that there are increases in ATLM's knowledge of laboratory management, especially ISO 9001:2015 after being given counseling. From the results of the activity, it is expected to increase understanding related to laboratory management, especially the ISO 9001:2015 standard.